Comparison of two serological diagnosis tests for bovine paratuberculosis - Tieri, Silvina; Morsella, Claudia Graciela; Mendez, Laura Luján; Vasini, B.; Garro, Carlos Javier; Paolicchi, Fernando (Springer, 2025)
Mycobacterium avium subsp. paratuberculosis (MAP) is the causal agent of paratuberculosis (PTBC), a chronic infectious granulomatous enteritis of ruminants. The PTBC diagnosis with commercial ELISA has limitations in sensitivity and specificity, and its results depend on the state of progress of the disease. This research aimed to evaluate two different ELISAs: (a) an “in-house” ELISA with a sonicated antigen obtained from a MAP I47 strain, and (b) a commercial ELISA. In total, the evaluated sample consisted of 394 bovine serum samples from 12 farms in Argentina with high (5–9%) and low (≤ 0.05%) prevalence of PTBC. The evaluation of the new antigen (2.5 µg/mL) was against a 1:50 dilution of the M. phlei faced sera. The cut-off point, sensitivity, and specificity determinations of both techniques were by ROC curve analysis. The area under the curve for the I47 ELISA was 0.9 (CI 95%, 0.93–0.97). With a cut-off point of 8.8%, the sensitivity was 84.3% and the specificity 96.6%. The agreement between both techniques was 0.7 (CI 95%, 0.6–0.8). These results indicate a high discriminative capacity to differentiate positive and negative bovine sera of MAP infection with the I47 ELISA. This result would represent an advantage to dispense with the imported kit.